HOXA7 plays a critical role in metastasis of liver cancer associated with activation of Snail. Issue 1 (December 2016) - Tang, Bo; Qi, Guangying; Sun, Xiaoyu; Tang, Fang; Yuan, Shengguang; Wang, Zhenran; Liang, Xingsi; Li, Bo; Yu, Shuiping; Liu, Jie; Huang, Qi; Wei, Yangchao; et al.
Abstract Background Liver cancer is one of the main causes of cancer-related death in human. HOXA7 has been proved to be related with several cancers. Method The expression levels of HOXA7 were examined by Western blot, qRT-PCR or ICH. MTT was used to detect the proliferative rate of liver cancer cells. The invasive abilities were examined by matrigel and transwell assay. The metastatic abilities of liver cancer cells were revealed in BALB/c nude mice. Results In this report, we revealed that HOXA7 promoted metastasis of HCC patients. First, increased levels of HOXA7 were examined in liver cancer especially in metastatic liver cancer. Moreover, higher expression level of HOXA7 was associated with poorer prognosis of liver cancer patients. Overexpression of HOXA7 significantly enhanced proliferation, migration, invasion in vitro and tumor growth and metastasis in vivo meanwhile silencing HOXA7 significantly inhibited the aboves abilities of liver cancer cells. In this research, we identified that HOXA7 performed its oncogenic characteristics through activatingSnail . Conclusion Collectively, we identify the critical role and possible mechanism of HOXA7 in metastasis of liver cancer which suggest that HOXA7 may be a potential therapeutic target of liver cancer patients.